The XVA of Financial Derivatives: CVA, DVA and FVA Explained - Lu, Dongsheng. (Financial Engineering Explained, 2015)
This latest addition to the Financial Engineering Explained series focuses on the new standards for derivatives valuation, namely, pricing and risk management taking into account counterparty risk, and the XVA's Credit, Funding and Debt value adjustments.